The assessment of reading speed at the word level in German for bilingual Arabic-German students in Germany - Naddaf, Esraa (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
Research indicates that the German reading abilities of children with migration backgrounds are generally inferior when compared to their monolingual German counterparts. Previous studies have primarily concentrated on Turkish-German bilingual children, with limited attention given to those who speak other first languages. Notably, the reading skills of bilingual Arabic-German children have yet to be thoroughly explored. This study aims to assess the German reading speed at the word level among bilingual Arabic-German students in Germany. A one-minute reading test was administered to a sample of 66 bilingual Arabic-German children, with a mean age of 9;02 years. One group of 33 children received instruction in both German and Arabic, while the other group of 33 received only German instruction in school, with Arabic being taught outside of school. The results indicated no significant differences between the groups regarding the German tasks, and neither group exhibited signs of difficulties in German literacy.